Membangun Budaya Baca Tulis di Desa Pangkalan Benteng : Gerakan Literasi Desa - Bambang Suprianto (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
The community service program "Village Literacy Movement: Building Reading and Writing Culture in Pangkalan Benteng Village" aims to enhance reading and writing skills and establish a literacy culture within the village community. The primary issue addressed is the low literacy rate, which limits access to information and educational opportunities. The methods used in this program include literacy training and various literacy activities such as group reading, writing competitions, and book discussions. The results show significant improvements in reading and writing skills among children and adults, increased reading interest, and the development of a stronger literacy culture. Community empowerment and the enhancement of local leadership capacity were also achieved through active involvement in the management and implementation of the program. This program demonstrates that a participatory approach and access to quality reading materials can effectively improve literacy and empower communities.